Analisis Profil Pelajar Pancasila Sub Elemen Disiplin Melalui Program Tahfidz Al Qur’an di Sekolah Dasar - Rohmatun, Dewi; Widiyono, Aan (EduInovasi: Journal of Basic Educational Studies, 2024)
This study aims to analyze the impact of the Al-Qur'an memorization program at SD Miftahussa'adah on the self-discipline of 4th-grade students as part of the Pancasila Student Profile. The research employs a qualitative approach with a descriptive method, involving observations, interviews with the principal and teachers, and documentation. The findings reveal that the structured and routine tahfidz program positively affects student discipline, including aspects of punctuality, consistency in memorization, and personal time management. The discussion highlights that tahfidz activities not only enhance memorization skills but also strengthen students' discipline, supporting the Merdeka Curriculum's goal of character development. The conclusion of the study is that the tahfidz program is effective in developing students' discipline. Recommendations include improving teaching methods, providing additional training for teachers, and conducting regular evaluations of the program to enhance its effectiveness in supporting the Pancasila Student Profile.